Productive and Non-productive Pathways for Synaptotagmin 1 to Support Ca2+-Triggered Fast Exocytosis - Kim, Jaewook; Shin, Yeon-Kyun (Frontiers in Molecular Neuroscience, 2017)
Ca2+-triggered SNARE-mediated membrane fusion is essential for neuronal communication. The speed of this process is of particular importance because it sets a time limit to cognitive and physical activities. In this work, we expand the proteoliposome-to-supported bilayer (SBL) fusion assay by successfully incorporating synaptotagmin 1 (Syt1), a major Ca2+ sensor. We report that Syt1 and Ca2+ together can elicit more than a 50-fold increase in the number of membrane fusion events when compared with membrane fusion mediated by SNAREs only. What is remarkable is that ~55% of all vesicle fusion events occurs within 20 msec upon vesicle docking. Furthermore, pre-binding of Syt1 to SNAREs prior to Ca2+ inhibits spontaneous fusion, but intriguingly, this leads to a complete loss of the Ca2+ responsiveness. Thus, our results suggest that there is a productive and a non-productive pathway for Syt1, depending on whether there is a premature interaction between Syt1 and SNAREs. Our results show that Ca2+ binding to Syt1 prior to Syt1’s binding to SNAREs may be a prerequisite for the productive pathway. The successful reconstitution of Syt1 activities in the physiological time scale provides new opportunities to test the current mechanistic models for Ca2+-triggered exocytosis.